Demystifying foundation phase teaching: Male student teachers’ motivation to enroll for B.ED. degree in foundation phase at a rural university - Ravhuhali, F.; Mashau, T.S.; Lavhelani, P.N.; Mudzielwana, N.P.; Mulovhedzi, S. (South African Journal of Higher Education, 2020)
The teaching profession at the foundation phase is historically dominated by female teachers. It is a societal belief that female teachers provide motherly love and care and are naturally soft towards infants compared to their male counterparts. This paper explores a new trend that is developing at a rural university where male student teachers are increasingly enrolling for a Bachelor of Education programme where they specialise in the foundation phase (FP). The paper gathered male student teachers’ views for choosing teaching in the foundation phase as a career at one rural university in Limpopo Province. A qualitative case study design was adopted in which a purposeful sample of sixteen (16) male first year B.Ed. student teachers participated by completing open-ended questions as the main data collection tool. Content analysed data reveal that even though male student teachers were intrinsically and altruistically motivated and positive about their FP career choice and hope to demystify FP teaching, a few of them admitted that FP was a default career choice. A longitudinal cohort study is recommended in order to decipher the motivations, experiences and career paths of male FP teachers.